The effect of denture cleansing solution (H2O2) on the water solubility of self-cured acrylic resin - Ibrahim, Irsan; Luthfia, Prima; Aryani, Widuri Julia (Padjadjaran Journal of Dentistry, 2018)
Introduction: Denture cleanser must be able to remove bacterial plaque layers, eliminate food debris, with non-toxic properties. Denture cleansing was performed by immersing the denture into a solution of H2O2. Continuous denture wear can lead to plaque accumulation of Candida albicans colonies thus causes denture stomatitis. There was a slight dimensional stability difference of the self-cured acrylic base compared to the heat-cured after immersion in water. This study was aimed to analyse the effect of denture cleansing solution (H2O2) on the water solubility of self-cured acrylic resin. Methods: Twenty-four specimens of self-cured acrylic resin sized 15 x 20 x 2 mm, were divided into the control group (n = 12) and the treatment group (n = 12). All specimens were then immersed in the aquadest (control group) and H202(treatment group) for 6, 8, and 10 hours consecutively. Result: The average water solubility of self-cured acrylic resin soaked in H2O2 solution at 6 hours was 0.0007 µg/mm3; at 8 hours was 0.0011 µg/mm3; and at 10 hours was 0.0013 µg/mm3. The average water solubility of self-cured acrylic resin soaked in aquadest solution at 6 hours was 0.0013 µg/mm3; at 8 hours was 0.0080 µg/mm3; and at 10 hours was 0.0125 µg/mm3. Conclusion: The water solubility of the self-cured acrylic resin immersed in the H2O2 solution for 6, 8, and 10 hours was still below the ISO standard.Keywords: Self-cured acrylic resin, H2O2, immersion time, water solubility.